Conceptualization matters : Crimes against humanity in criminal law of the Republic of Azerbaijan - Shahniyarov, Tofig (ADA University, 2022)
The first national prosecution of international crimes in Baku Military Court proved national criminal law to be omitted certain internationalizing elements of crimes against humanity, namely the “State or organizational policy” and “the knowledge of the attack” requirements. In turn, the explanatory note of the Criminal Code of the Republic of Azerbaijan related to crimes against humanity provides a vague definition of those crimes. This shortcoming derives from the conceptualization of these crimes in domestic criminal law and makes it difficult to differentiate such crimes from ordinary criminality. It also undermines the generally recognized principles and norms of international law and, thereby, the functionality of international criminal justice in the national jurisdiction. This paper then argues that the criminal law of the Republic of Azerbaijan should reflect the current features of customary international law with regard to crimes against humanity by incorporating the “State or organizational policy” and “the knowledge of the attack” requirements into the Criminal Code.
Keywords: Crimes against humanity.; International crimes.; Criminal law.; Public and International Affairs